"Let's talk about sex": visitor comments in Contraception: Uncovering the collection of Dame Margaret Sparrow. (January 2017) - Gibson, Stephanie
Abstract: Contraception: Uncovering the collection of Dame Margaret Sparrow was an exhibition at the Museum of New Zealand Te Papa Tongarewa which featured a participatory activity titled "Let's talk about sex" where visitors could answer the question: "If you could give your younger self one piece of advice about contraception, what would it be?" Over 2200 comments were written, inspiring an evaluation project. The resulting analysis provides insights into visitors' attitudes, values, behaviours, experiences and concerns about contraception, sex, sexuality and sexual health in the early 21st century. The results also demonstrate the value and usefulness of visitor comments both as an exhibition experience and as data to complement formal evaluation methods. The paper also acknowledges the less successful aspects of the project.